Rifting episode in north iceland in 1874-1875 and the eruptions of askja and sveinagja - Sigurdsson, H.; Sparks, R. S.J. (Bulletin Volcanologique, 1978)
In 1874 and 1875 the fissure swarm of Askja central volcano was activated during a major rifting episode. This rifting resulted in a fissure eruption of 0.3 km3 basaltic magma in Sveinagja graben, 50 to 70 km north of Askja and subsequent caldera collapse forming the Oskjuvatn caldera within the main Askja caldera. Five weeks after initial collapse, an explosive mixed magma eruption took place in Askja. On the basis of matching chemistry, synchronous activity and parallels with other rifted central volcanoes, the events in Askja and its lissure swarm are attributed to rise of basaltic magma into a high-level reservoir in the central volcano, subsequent rifting of the reservoir and lateral flow magma within the fissure swarm to emerge in the Sveinagja eruption. This lateral draining of the Askja reservoir is the most plausible cause for caldera collpse. The Sveinagja basalt belong to the group of evolved tholejites characteristie of several Icelandic central volcanoes and associated fissure swarms. Such tholeiites, with Mgvalues in the 40 to 50 tange, represent magmas which have suffered extensive fractional crystallization within the crust. The 12% porphyritic Sveinagja basalt contains phenocrysts of olivine (Fo62-67), plagioclase (An57-62), clinopyroxene (Wo38En46Wo16) and titanomagnetite. Extrusion temperature of the lava, calculated on the basis of olivine and plagioclase geothermometry, is found to be close to 1150°C. © 1978 Intern. Association of Volcanology and Chemistry of the Earth's Interior.